2016
DOI: 10.1016/j.physbeh.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Higher insulin and higher body fat via leptin are associated with disadvantageous decisions in the Iowa gambling task

Abstract: Elevated body mass index and post-prandial state are associated with disadvantageous choices on the Iowa Gambling Task (IGT). Whether physiological factors including percent body fat, and peripheral glucose, insulin, and leptin concentrations, are associated with IGT performance is unknown. In 196 healthy adults without diabetes, we measured body fat by DXA scan, glucose, insulin and leptin (n=138) concentrations during an oral glucose tolerance test and IGT performance after a standardized meal. Glucose was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…One possible explanation for these findings is that increases in perseveration could intensify cognitive restraint, thereby contributing to more binge cycles in obesity [10]. Studies from our lab have also shown that higher leptin levels, commonly associated with greater percent body fat and increased food intake as seen in obesity [37] correlated to disadvantageous performance on the Iowa Gambling Task (IGT), a measure of decision making [38]. Higher scores on the IGT were associated with a greater amount of weight loss in obese women [27].…”
Section: Executive Functionmentioning
confidence: 83%
“…One possible explanation for these findings is that increases in perseveration could intensify cognitive restraint, thereby contributing to more binge cycles in obesity [10]. Studies from our lab have also shown that higher leptin levels, commonly associated with greater percent body fat and increased food intake as seen in obesity [37] correlated to disadvantageous performance on the Iowa Gambling Task (IGT), a measure of decision making [38]. Higher scores on the IGT were associated with a greater amount of weight loss in obese women [27].…”
Section: Executive Functionmentioning
confidence: 83%